If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -65 + -1x = -6x + 20 Reorder the terms: -65 + -1x = 20 + -6x Solving -65 + -1x = 20 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -65 + -1x + 6x = 20 + -6x + 6x Combine like terms: -1x + 6x = 5x -65 + 5x = 20 + -6x + 6x Combine like terms: -6x + 6x = 0 -65 + 5x = 20 + 0 -65 + 5x = 20 Add '65' to each side of the equation. -65 + 65 + 5x = 20 + 65 Combine like terms: -65 + 65 = 0 0 + 5x = 20 + 65 5x = 20 + 65 Combine like terms: 20 + 65 = 85 5x = 85 Divide each side by '5'. x = 17 Simplifying x = 17
| x-16=-22x | | 17(6c-1)-10=100c+17 | | 4x^3-456x=0 | | -81+12x=171-9x | | 3x+7=11+2x | | h(x)=-x^4+5x^2-4 | | 2x+0.5x-10=10 | | w^2+10w-2475=0 | | 8/5(t-6)=0.4 | | -x-58=-6x+47 | | .5x+3.5=4x-7 | | 2x^2-12x-56=0 | | 5x-63=-3x+33 | | 54/100 | | 4/12=18/x | | 1/4q=20 | | -19-7x=39-9x | | 2.20x=12 | | -5(t-1)+7t=5t-3 | | log(10-4x)=log(10x-3x) | | 1/2*2/67 | | 4P=T-5R+6forR | | 7x-35=28+4x | | 4x(2x-1)=7 | | 5x+2-7(x+1)=7x+2 | | 3+6x=27+6 | | -63-x=-7x+27 | | x^2+5y+4=0 | | 285=31.4159h+314.159 | | 3x+6x=27+6 | | 7x+6-5(x+1)=9x+5 | | 7x^2+14x-28=0 |